Active Vibration Control of a Thin Steel Sheet - Yohji Okada; Ken-Ichi Matsuda; Junji Tani (Shock and Vibration)
The commercial rolling process used in the steel industry to manufacture thin steel sheets tends to cause plate vibrations that lower the quality of the surface finish. This article introduces a noncontact method of active vibration control for reducing the flexural vibrations of a thin steel sheet. The proposed electromagnetic method of control has been implemented in a simple experimental setup where the signal from a motion sensor regulates the attractive force of the magnets that produce a damping force on the steel sheet.